2010
DOI: 10.1111/j.1532-950x.2010.00680.x
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Dynamics Analysis of the Pelvic Limbs in Labrador Retrievers With and Without Cranial Cruciate Ligament Disease

Abstract: Reductions in joint motion, loads, and muscle contraction were interpreted as modifications adopted to reduce or avoid painful mobilization of the injured stifle joint. The increased joint moment and power of the contralateral compensating side may correlate with the lameness observed, but also with the predisposition of contralateral limbs to CCL deficiency in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(92 citation statements)
references
References 28 publications
5
86
1
Order By: Relevance
“…During this phase of the gait, the mean flexor moment impulse of the stifle joint for the dogs in the TPLO and LFS groups was increased from that for dogs in the control group. 12 In the present study, the only variable that differed significantly among the 3 groups of dogs aside from the hip joint angle in the sagittal plane at the onset of the stance phase was the maximum concentric power of the stifle joint in the frontal plane; the maximum concentric power of the stifle joint for the dogs of the LFS group was approximately 8.6 times that for the dogs in the control group. It would be interesting to study this area of the stifle joint moment curve at various times during re- Table 1 for key.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…During this phase of the gait, the mean flexor moment impulse of the stifle joint for the dogs in the TPLO and LFS groups was increased from that for dogs in the control group. 12 In the present study, the only variable that differed significantly among the 3 groups of dogs aside from the hip joint angle in the sagittal plane at the onset of the stance phase was the maximum concentric power of the stifle joint in the frontal plane; the maximum concentric power of the stifle joint for the dogs of the LFS group was approximately 8.6 times that for the dogs in the control group. It would be interesting to study this area of the stifle joint moment curve at various times during re- Table 1 for key.…”
Section: Discussioncontrasting
confidence: 42%
“…Although the use of inverse dynamics in veterinary medicine is relatively novel, compared with its use in ABBREVIATIONS CCL Cranial cruciate ligament LFS Lateral fabellar-tibial suture TPLO Tibial plateau leveling osteotomy human medicine, numerous studies [1][2][3][4][5][6][7][8][9][10][11][12] have been conducted to analyze the gait of various species of veterinary interest. Results of those studies [1][2][3][4][5][6][7][8][9][10][11][12] have aided in the elucidation not only of the normal movement of animals, but also possible factors associated with the pathogenesis of musculoskeletal disease and injury.…”
mentioning
confidence: 99%
“…However, our results suggest that the aforementioned areas were possibly responsible for a higher percentage of weight bearing and for the braking and propulsion vertical force peaks. This may be related to CCLR given the braking phase of the stride is one of the most affected by the instability of the joint due to the cranial movement of the tibia [28], as simulated during physical examination using the tibial thrust test [29]. Vertical force magnitude in metatarsal pad may thus constitute an important parameter for post-surgical follow-up of CCLR cases.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, depending on the cause of lameness, the two phases of the fore-aft forces –braking (Fy-) and propulsion (Fy+)– may be affected differently. For example, it has been shown that in dogs with cranial cruciate ligament disease, although both phases were affected [27], the braking force was more affected than the propulsive force in order to avoid tibial thrust during early stance [30]. Dogs with a unilateral fragmented coronoid process showed more pronounced alterations in the propulsive than the braking force likely due to limited elbow extension during late stance phase [3].…”
Section: Introductionmentioning
confidence: 99%